Temperature-dependent anharmonic effects on shear deformability of Bi2Te3 semiconductor. (September 2021) - Huang, Ben; Li, Guodong; Duan, Bo; Zhai, Pengcheng; Goddard, William A.
Abstract: For performance stability and wearable application of Bi2 Te3 thermoelectric (TE) semiconductors, it is necessary to enhance its deformability at the operating temperature. Given Van der Waals sacrificial bond (SB) behavior in Bi2 Te3 crystals, temperature-dependent anharmonic effects on the structural evolution and mechanical performance during shearing is studied through molecular dynamics simulations. With increasing temperature, in addition to larger difference of initial bond strength, the synergy between SB and defect during slipping tends to be suppressed, resulting in strain localization with less crystal deformability. The temperature-induced change of nanocrystal deformation modes is clearly identified by the growth trend difference of deformation heterogeneity parameter ( F ) that is defined according to configurational energy distribution. This simulation work provides new insights into the role of sacrificial bonds and substructures on synergistically deformability tuning, likely improving defect engineering strategy for designing advanced multi-scale hierarchical TE semiconductors.